IMPLEMENTATION OF DIGITAL TECHNOLOGIES INTO SERVICEMEN FINANCIAL SUPPORT SYSTEM OF THE ARMED FORCES OF UKRAINE - Gorodianska, L. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
The article deals with the areas of digital transformation of servicemen financial support system of the Armed Forces of Ukraine under martial law in accordance with the course of NATO standards implementation in the military sphere. The expediency of optimizing the procedure for calculating cash payments to servicemen by introducing digital technologies into servicemen financial support security system of the Armed Forces of Ukraine is substantiated. The solution of the problem requires a comprehensive approach and determination of the ways of reforming the Ukrainian digital space in order to create an online portal for the provision of social services for servicemen. In order to find ways to organize remote and operational access of servicemen to own financial information, a study of modern classical technologies (3.0+) and new technologies (4.0) was conducted. A number of digital transformation technologies of the system of financial support of the servicemen of the Armed Forces of Ukraine as promising directions of reforming the Ukrainian digital space have been identified. Based on the results of an analytical review of a number of regulatory and legal documents, the components of the financial support system of the Armed Forces of Ukraine in wartime conditions were clarified and, as a result, a model for the introduction of digital technologies was formulated according to the outlined directions of transformation. A mechanism has been defined that requires the improvement of the procedure for the organization of military financiers at all levels of military administration and their coordinated interaction with specialists of state institutions with the aim of introducing digital technologies to the Center for the Provision of Administrative Services of Ukraine.